The Deaf Students’ in Writing English Text by Using Recount Text - Tarigan, Sri Ninta (Journal of Applied Linguistics, 2021)
The problem of this study is how Recount Text application in writing English text was and what the obstacle was. The purpose of this research is to find how Recount Text application in writing in English was and to find out what the obstacles was. The method used in this research was qualitative method in the form of case studies. The population was students of SLB Taman Pendidikan Islam. The number of students consists of 7 students and the whole will be sampled in the study. The conclusion of this research was found that recount text need more practice. It means that the application of recount text was not implicate well in Extraordinary School (SLB) Taman Perguruan Islam Medan. Teacher should be given many vocabularies. Vocabularies were the important things in writing text. How students able write well if they did not have vocabulary references. The solution of this problem was deaf students should be given short story so they can not only enjoy the story but also have many vocabulary references. The location of this research was in the Disable School (SLB) ABC Taman Pendidikan Islam (TPI) which was located at Jl. Sm. Raja Km. 7 no.5 Harjosari Medan. The conclusion of this research was found that recount text need more practice. It means that the application of recount text was not implicate well in Extraordinary School (SLB) Taman Perguruan Islam Medan. Keywords: writing achievement, recount text, kids with special needs